Returning Serve in Tennis: A Qualitative Examination of the Interaction of Anticipatory Information Sources Used by Professional Tennis Players - Vernon, Georgina; Farrow, Damian; Reid, Machar (Frontiers in Psychology, 2018)
Research has largely focused on the individual contribution of either kinematic or contextual information sources to the anticipatory skill of an expert athlete during a time-stressed situation. Very little research has considered how these two sources of information interact with each other to influence anticipation. The current study used a qualitative interview methodology to investigate this interaction. Eight former or current top 250 professional male tennis players participated in a 30-60 minute interview about the interaction of kinematic and contextual information sources and their influence on anticipation. Using an open-coding analysis approach, codes were identified by each researcher from the transcribed interviews and then brought together to identify common themes. The primary themes were consciousness, tactical awareness, contextual information sources, kinematic information sources, mentality/confidence, returner technique or strategy, and build pressure on the server. Secondary themes coded from the participants were returning characteristics and practice. Consequently, a temporal model was developed which demonstrated the sequence and interaction of both kinematic and contextual information sources known to influence expert tennis players anticipation.